Short-term impact of PM2.5 fine particulate pollution on the ventilatory function of adults jogging in Porto-Novo in Benin. - AHOUNOU AÏKPE, FIFAMIN JUDITH; Gbaguidi, Magloire A. N.; GODONOU, Jean-Bénoit; Gbénou, Joachim D.; DANSOU, Pierre H.; Zannou, Aimé (My University, 2017)
Position of the problem: Air pollution in general has become one of the major problems today that threatens the daily health of the Beninese population and undermines the stability of the affected ecosystems. The rapid development of motorcycle taxis, the explosion of the used vehicle sector emitting particulate matter from exhaust gases and/or taxiways, and the consequences of poor household waste management, especially in large cities of Benin have amplified the magnitude of the phenomenon. Thus, the persistent presence of an opaque mixture of smoke, dust and moisture on the main arteries and at the major crossroads of the city centers during peak hours was noted. The aim of the research was to study the effects of short-term exposure of air pollutants on ventilatory function during the physical exercise of adults engaged in jogging in traffic. Methods: Measurements of Particulate Matter (PM) were carried out at the sport site from 06 H to 20 H using a KNF membrane vacuum pump and a filter device equipped with a filter depth of quartz fiber Whatman cat.n. 1852047, QMA grade, Ø: 47 mm and Millipore AQFA code, Ø: 47 mm. The membranes were stored at 20 °C. ± 2 °C. for 48 hours and weighed under vacuum before and after measurement on site. Functional exploration was also performed for the determination of the ventilatory parameters of the subjects. Results: The results obtained showed that the concentration of particles with an aerodynamic diameter of less than 2.5 μm was higher than that of the particles with an aerodynamic diameter greater than 2.5 μm in the jogging environment. Analysis of ventilatory parameters revealed that exposure to particles over a short period of time did not have a significant effect on the health of the subjects. Nevertheless, a long-lasting physical practice or repetitive in time and space, could therefore prove detrimental for these weekend maintenance sports practitioners. Conclusion: The environment in which adults engaged in jogging was heavily concentrated in fine particles (PM2.5). The frequent exposure to these particles can therefore create respiratory pathologies because they are aggressive and penetrate rapidly in the deep regions of the lungs.
Keywords: PM2.5; respiratory function; physical activity; short term effect